Mitochondrial Dysfunction: Effects and Therapeutic Implications in Cerebral Gliomas - Gerardo Caruso; Roberta Laera; Rosamaria Ferrarotto; Cristofer Gonzalo Garcia Moreira; Rajiv Kumar; Tamara Ius; Giuseppe Lombardi; Maria Caffo (Medicina)
Gliomas are the most common primary brain tumors, representing approximately 28% of all central nervous system tumors. These tumors are characterized by rapid progression and show a median survival of approximately 18 months. The therapeutic options consist of surgical resection followed by radiotherapy and chemotherapy. Despite the multidisciplinary approach and the biomolecular role of targeted therapies, the median progression-free survival is approximately 6–8 months. The incomplete tumor compliance with treatment is due to several factors such as the presence of the blood–brain barrier, the numerous pathways involved in tumor transformation, and the presence of intra-tumoral mutations. Among these, the interaction between the mutations of genes involved in tumor bio-energetic metabolism and the functional response of the tumor has become the protagonist of numerous studies. In this scenario, the main role is played by mitochondria, cellular organelles delimited by a double membrane and containing their own DNA (mtDNA), which participates in numerous cellular processes such as the regulation of cellular metabolism, cellular proliferation, and apoptosis and is also the main source of cellular energy production. Therefore, it is understood that the mitochondrion, specifically its functional alteration, is a leading figure in tumor transformation, including brain tumors. The acquisition of mutations in the mitochondrial DNA of tumor cells and the subsequent identification of the so-called mitochondria-related genes (MRGs), both functional (mutation of Complex I) and structural (mutations of Complex III/IV), have been seen to play an important role in metabolic reprogramming with increased proliferation, resistance to apoptosis, and the progression of tumorigenesis. This demonstrates that these mitochondrial alterations could have a role not only in the intrinsic tumor biology but also in the extrinsic one associated with the therapeutic response. We aim to summarize the main mitochondrial dysfunction interactions present in gliomas and how they might impact prognosis.